DESAIN PENGEMBANGAN SISTEM MONITORING KEDALAMAN PERAIRAN BERBASIS USV : Menggunakan Unmanned Surface Vehicle (USV) Berbasis Sonar Deeper Pro+ - LOUIS BRIANT AGATA SIAHAAN; DIANA ALIA; AKHMAD KASAN GUPRON (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2026)
Information regarding water depth and seabed morphology is essential in hydrographic surveys to support navigational safety, the monitoring of shipping channels, and the management of water bodies. This study aimed to develop a depth mapping system by integrating a Deeper Pro+ sonar, the Fish Finder application, and an Unmanned Surface Vehicle (USV) as the sensor-carrying platform. The research employed the Research and Development (R&D) method using the ADDIE model. Testing was conducted in the swimming pool and training pool at the Surabaya Merchant Marine Polytechnic, utilizing both radial and parallel sounding patterns. Each combination of location and pattern yielded 30 measurement points. Results from the swimming pool tests revealed three dominant depth zones: approximately 1.0 m, 2.0 m, and 4.5 m. In the training pool, the radial pattern yielded depths ranging from 1.7 m to 6.5 m (average 4.64 m), while the parallel pattern yielded depths ranging from 1.4 m to 6.5 m (average 4.62 m). The radial pattern highlighted depth variations toward the central area, whereas the parallel pattern provided a more uniform data distribution. The integration of the sensor, positioning system, mapping application, and USV successfully generated depth data and bathymetric visualizations in relatively calm waters.